Comprehensive Analysis of AI's Contribution to Global Economic Development - Abdur Rohman; Asfahani Asfahani; Khurshed Iqbal; Loso Judijanto; Rony Sandra Yofa Zebua (Journal of Artificial Intelligence and Development, 2023)
This article presents a comprehensive analysis of the contribution of artificial intelligence (AI) to global economic development. This research aims to fill the knowledge gap by presenting a comprehensive analysis of the contribution of AI to global economic development. The method used in this research involves a comprehensive approach that includes literature analysis, case studies, and evaluation of the latest global economic data. Through a holistic approach, this research explores the impact of AI from various perspectives, including economic growth, labor markets, ethical aspects, and social implications. The research results show that the widespread implementation of AI technology has positively impacted productivity and efficiency in various sectors, driving significant GDP growth. However, inequality in access and benefits of AI technology has also been found, requiring special attention in global policy formulation. Through pairing with previous research and integrating economic and innovation theory, this article provides deep insight into the complexity of the interactions between AI and global economic development. In doing so, this article not only enriches our understanding of the role of AI in a global context but also details how relevant theories can be updated to reflect the evolving dynamics of AI's dominance in the global economic landscape.